The impact of Institutional Quality on Poverty, Income Inequality and Unemployment in Sub-Saharan African Countries - Ahmed, Umar Abdullahi (2024)
Despite numerous policies and initiatives implemented by Sub-Saharan African countries to address developmental challenges such as poverty reduction, income inequality, and unemployment, these issues persist as significant obstacles to progress in these countries. The limited success of these efforts underscores the critical importance of examining the role of institutional quality in achieving these development goals. This study investigates the impact of institutional quality on poverty levels, income inequality, and youth unemployment in Sub-Saharan African countries. Utilizing secondary data spanning from 1984 to 2018, the research employs the advanced second-generation estimation technique developed by Driscoll and Kraay. The findings reveal that strong institutional quality arrangements reduce poverty and income inequality in Sub-Saharan African countries. Corruption exacerbates poverty, while improved bureaucratic quality, government stability, and overall institutional quality contribute to poverty reduction. However, stronger law and order and increased corruption are associated with higher inequality, whereas government stability, democratic accountability, and overall institutional quality help mitigate it. Additionally, various institutional factors, including corruption, bureaucratic quality, government stability, democratic accountability, and the institutional quality index, positively correlate with youth unemployment. The governments and policymakers of Sub-Saharan African countries should design and implement robust policies to enhance their institutional frameworks. Furthermore, national policies should explicitly incorporate pro-poor strategies in economic growth, trade openness, and financial development. Establishing a credible policy framework that bolsters institutional arrangements is essential to support economic development and effectively address the persistent challenges of poverty, income inequality, and youth unemployment in Sub-Saharan African countries. This study aligns with the institutions-augmented Solow growth theory, stating the vital role of institutional arrangements in achieving sound economic development